BIOGAS PLANTS AS AN ELEMENT OF PROSUMER ENERGY DEVELOPMENT IN THE EUROPEAN UNION - Zawada, Marcin; Kowalik, Jan; Kucęba, Robert (PEOPLE: International Journal of Social Sciences, 2017)
The aim of this study is to assess the situation on the market for biogas plants in the EU, an analysis of the environmental benefits of the construction of agricultural biogas plants and the prospects for the development of this industry in the context of the prosumer energy. In the first part of this article the Authors provide basic information about agricultural production of gas in the European Union (total installed capacity, the number of biogas plants, different types of biogas plants, types of substrates used to feed the Biogas plants). The second part of the study provides an overview of the legislation governing prosumer energy and development of this element of the energy market which is an important and permanent part of the EU energy policy. In the third part of this paper the conducted SWOT analysis shows the strengths and weaknesses of the biogas energy, as well as the opportunities and threats of its further development. The scope of the research covers the period 2007-2015. In order to assess biogas plants market development, the Authors have used elements of multivariate statistical analysis and applied Herfindahl-Hirschman Index assessing the degree of concentration in this market.